29 Bivalirudin in patients undergoing primary percutaneous coronary intervention for acute ST-elevation myocardial infarction: outcomes in a large real-world UK population. (9th June 2011) - Eftychiou, C; Shelton, R J; Liu, A; Somers, K; Tooze, P; Makri, L; Barmby, D; McLenachan, J M; Blaxill, J M; Wheatcroft, S B; Greenwood, J P; Blackman, D J
Abstract : Background: The HORIZONS-AMI trial demonstrated a significantly lower early and late mortality in patients undergoing primary PCI (PPCI) treated with bivalirudin compared to a Glycoprotein IIb/IIIa inhibitor (GPI) + heparin. However, concerns remain regarding the increased incidence of acute stent thrombosis (ST) with bivalirudin, the apparently worse outcomes in the absence of additional pre-procedural heparin, and the translation of trial results into a real-world population. We evaluated the outcomes of patients undergoing PPCI with bivalirudin in a large all-comers UK setting. Methods: All patients who underwent PPCI in Leeds General Infirmary from 1 January 2009 to 31 December 2009 were prospectively entered into a dedicated registry. Demographic, procedural, and 30-day outcome data were obtained by abstraction from the ONS mortality database and BCIS PCI database, review of hospital notes, and telephone follow-up. Bivalirudin was administered as a bolus, high-dose intra-procedural infusion, and low-dose infusion for 4 h post-PCI. Additional heparin was not routinely given, but was favoured by some operators. Bail-out GPI was administered according to physician judgement. Primary endpoints were death, MACE (death, re-infarction, stroke, unplanned target vessel revascularisation (TVR)), and stent thrombosis (ST) (ARC definition definite/probable) at 30-days follow-up. Results: 968 patients (age 63.5±13 years, 71.9% male, 13.2% diabetics) underwent PPCI. Bivalirudin was given in 882 patients (91.1%), and GPI + heparin in 85 (8.8%). Of bivalirudin-treated patients 100 (11.3%) also received heparin (29 pre-PCI and 80 during) while bail-out GPI was used in 91 (10.3%). Thirty-day outcomes are shown in Abstract 29 table 1 . All-cause mortality was 5.2% in the bivalirudin treated patients. Acute ST occurred in 1.0%, a median of 2 h post-PCI, and within 6 h in 90%. Mortality in patients who suffered acute ST was 20%, compared to 80% following subacute ST. There was no difference in outcomes between bivalirudin treated patients who also received heparin compared to those who didn′t (death 7.0% vs 5.0%, p value: 0.80; MACE 14.0% vs 10.8%, p value: 0.32; acute ST 0% vs 1.2%, p: 0.61). Conclusion: Routine use of bivalirudin in a large UK all-comers primary PCI population was associated with excellent 30-day outcomes, including all-cause and cardiac mortality. Acute stent thrombosis was infrequent, despite the absence of routine additional heparin.